Deferred Tax Expense and Tunneling Incentive Influence on Tax Avoidance via Transfer Pricing - Maghfirah Armadhana, Annisa Nur; Santika, Sisca; Khairiyah, Nurul Musfirah (JURNAL AKUNTANSI DAN AUDITING, 2025)
This research aims to analyze the effect of Deferred Tax Expense and Tunneling Incentives on Tax Avoidance with Transfer Pricing as an intervening variable in multinational companies located in Indonesia. This study uses a quantitative approach with secondary data from 17 multinational companies listed on the OECD website during the period of 2022–2024. The analytical technique used is path analysis to test the direct and indirect relationships between variables. The research results indicate that simultaneously, Deferred Tax Expense and Tunneling Incentive have an influence on Tax Avoidance. Partially, the Deferred Tax Expense has a negative impact on Tax Avoidance, Tunneling Incentive does not affect Tax Avoidance, Deferred Tax Expense does not affect Transfer Pricing, Tunneling Incentive does not affect Transfer Pricing, Transfer Pricing cannot mediate the effect of Deferred Tax Expense on Tax Avoidance, and Transfer Pricing cannot mediate the effect of Tunneling Incentive on Tax Avoidance.